Central Bank communication with the general public: Promise or false hope? - Alan S. Blinder; Michael Ehrmann; Jakob de Haan; David-Jan Jansen (European Central Bank (ECB), 2022)
Central banks are increasingly reaching out to the general public to motivate and explain their monetary policy actions. One major aim of this outreach is to guide inflation expectations; another is to ensure accountability and create trust. This article surveys a rapidly-growing literature on central bank communication with the public. We first discuss why and how such communication is more challenging than communicating with expert audiences. Then we survey the empirical evidence on the extent to which this new outreach does in fact affect inflation expectations and trust. On balance, we see some promise in the potential to inform the public better, but many challenges along the way.
Keywords: D12; D84; E52; E58; G53; 330; communication; central bank; general public; monetary policy